House made of dawn - Momaday, N. Scott, 1934- (Perennial Classics, 1999)
The magnificent Pulitzer Prize-winning novel of a proud stranger in his native land. He was a young American Indian named Abel, and he lived in two worlds. One was that of his father, wedding him to the rhythm of the seasons, the harsh beauty of the land, the ecstasy of the drug called peyote. The other was the world of the twentieth century, goading him into a compulsive cycle of sexual exploits, dissipation, and disgust. Home from a foreign war, he was a man being torn apart, a man descending into hell.